2012
DOI: 10.1242/jcs.105528
|View full text |Cite
|
Sign up to set email alerts
|

CCN2/CTGF increases expression of miR-302 microRNAs, which target the TGFβ type II receptor with implications for nephropathic cell phenotypes

Abstract: SummarySignalling interplay between transforming growth factor-b (TGFb) and CCN2 [also called connective tissue growth factor (CTGF)] plays a crucial role in the progression of diabetic nephropathy and has been implicated in cellular differentiation. To investigate the potential role of microRNAs (miRNAs) in the mediation of this signalling network, we performed miRNA screening in mesangial cells treated with recombinant human CCN2. Analysis revealed a cohort of 22 miRNAs differentially expressed by twofold or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 64 publications
0
48
0
1
Order By: Relevance
“…In summary, recent studies have described the complex relationship between increased CTGF expression, TGFb activity, and fibrotic pathogenesis, 45,69,70 highlighting the complex signaling interplay between CTGF and TGFb that results in increased production of ECM components. It is now clear that the fibrotic/permissive microenvironment in the glaucoma AqH contains sizable quantities of both factors.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, recent studies have described the complex relationship between increased CTGF expression, TGFb activity, and fibrotic pathogenesis, 45,69,70 highlighting the complex signaling interplay between CTGF and TGFb that results in increased production of ECM components. It is now clear that the fibrotic/permissive microenvironment in the glaucoma AqH contains sizable quantities of both factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-302 could suppress the TGF-β-induced EMT of human epithelial cells, through regulating the expression of E-cadherin and ZO-1 [20]. In renal HKC8 epithelial cells, miR-302d decreased TGF-β-induced EMT and attenuated TGF-β-induced mesangial production of fibronectin and thrombospondin by negative regulation of TbRII receptor [35]. In human prostate cancer cells (PC-3 cells), dsEcad640, which is a siRNA, suppressed the expression of ZEB1 mRNA and upregulated the expression of E-cadherin through combination with ZEB1 coding sequence, and dsEcad640 and miR-302a have the same seed sequence [20].…”
Section: Discussionmentioning
confidence: 99%
“…TbRII down-regulation enhances the dedifferentiation process and promotes a mesenchymal to epithelial transition that is required for the establishment of the stem cells in vitro. In a different context, miR-302, which is induced by connective tissue growth factor ([CTGF] also called CCN2), targets TbRII mRNA and thereby inhibits kidney fibrosis (Faherty et al 2012). On the other hand, during progression of kidney fibrosis, TGF-b signaling transcriptionally represses the miR-let-7b (commonly known as let-7b); miR-let-7b targets and down-regulates TbRI mRNA expression, and, thus, miR-let-7b repression by TGF-b causes TbRI induction and enhanced signaling in kidneys where fibrosis develops Wang et al 2014).…”
Section: Control Of Tgf-b Receptor Expression By Micrornasmentioning
confidence: 99%